Kinetics and Mechanism of Chlorination of Some ketones by Chloramine-B - Yathirajan, H.S.; R. Nadig, Aparna; Mohana, K.N. (Asian Journal of Chemistry, 2010)
The kinetics of chlorination of acetone'(AC), ethyl methyl ketone(EMK), ethyl phenyl ketone (EPK), methyl isobutyl ketone (MIK),diethyl ketone (DEK), acetophenone (A), 3',4'-dirnethoxyacetophenone (DMA) and p-hydroxy acetophenone (HA) by sodiumN-chlorobenzenesulphonamide (Chloramine-B or CAB) inhydrochloric and perchloric acid media has been carried out at 30°C.The effect of [H+] and [CI-], variation of ionic strength anddielectric constant to the medium on the rate of reaction has beenstudied, Addition of the reaction product, benzenesulphonamide hadno effect on the rate of chlorination. Thermodynamic parametershave been evaluated by studying the kinetics at various temperatures.Suitable mechanisms have been proposed in consistency withthe kinetic results.